Culinary Innovation: Crackers Innovation Using Jatiluwih Red Rice Tea Dregs - Tanius, Billy; Pramudia, Heru; Riyanto, Budi (E-Journal of Tourism; Volume 10 Number 2 (September 2023), 2023)
This study aimed to develop processed cracker products made from brown rice flour dregs. This research was experimental research. Based on the experimental results, brown rice tea dregs can be developed into three types of crackers that have different colors, aromas, tastes, textures & crispness, and shapes. Crackers were produced using the same method but with the addition of different ingredients; crackers A used wheat flour, crackers B used tapioca flour, and crackers C used brown rice flour. The organoleptic test involved 62 respondents who were asked to provide an assessment of the crackers produced. Based on the organoleptic test, it can be seen that in terms of texture and crunchiness, people liked crackers C the most, in terms of taste the people also liked crackers C the most, in terms of color the people liked the color of crackers B the most, in terms of smell the people liked the aroma of crackers C the most , and in terms of form, the community liked cracker B the most.